Enhancing wheat productivity, quality and nutrient uptake through application of phosphate rich organic manure and soil amendments under Typic Hapludalfs - Ranjha, Rewangini; Dhanbir Singh; Sanjay K Sharma; Pankaj Chopra (Journal of Cereal Research, 2024)
The present investigation was undertaken at Experimental Farm of Department of Soil Science, CSK Himachal Pradesh Agricultural University, Palampur to study the effect of phosphate rich organic manure and soil amendments like FYM and lime on wheat productivity, quality and nutrient uptake. The experiment was laid out in Randomized Block Design with nine treatments and were replicated three times. The highest grain yield (38.7 qha-1), straw yield (62.7 qha-1) and P uptake (28.5 kgha-1) were observed in the treatment receiving 50% recommended dose of phosphorus from inorganic fertilizer + phosphate rich organic manure (PROM) @ 1.5 tha-1 along 100 % NK. The maximum crude protein content (12.9 %), P content (0.54 %), K content (0.39 %) was also recorded under same treatment. Application of farm yard manure and lime along with 100 % NPK also improved crop productivity, quality and nutrient uptake as compared to solo application of inorganic fertilizers.